Existence and Exponential Stability of Positive Almost Periodic Solutions for a Model of Hematopoiesis. (27th September 2009) - Alzabut, J. O.; Nieto, J. J.; Stamov, G. Tr.
Abstract : By employing the contraction mapping principle and applying Gronwall-Bellman's inequality, sufficient conditions are established to prove the existence and exponential stability of positive almost periodic solution for nonlinear impulsive delay model of hematopoiesis.